2019
DOI: 10.1142/s0219455419501050
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Slenderness and Fundamental Frequency on the Dynamic Response of Adjacent Structures

Abstract: In conventional seismic design, the structure is often assumed to be fixed at the base. However, this assumption does not reflect reality. Furthermore, if the structure has close neighbors, the adjacent structures will alter the response of the structure considered. Investigations on soil–structure interaction and structure–soil–structure interaction have been performed mainly using numerical models. The present work addresses the dynamic response of adjacent single-degree-of-freedom models on a laminar box fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To summarize, this outcome is compatible with the study finding of Aldaikh et al [4], which indicated that a structure seems to experience the most unfavorable interaction influence when bounded by one or two higher buildings by about 10%. This result also agrees with the result of Barrios et al [7], which showed that whenever the slenderness increases, the resulting acceleration increases also. Figure 6 compares the building top displacement response of a three-story building against adjacent buildings with different heights.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…To summarize, this outcome is compatible with the study finding of Aldaikh et al [4], which indicated that a structure seems to experience the most unfavorable interaction influence when bounded by one or two higher buildings by about 10%. This result also agrees with the result of Barrios et al [7], which showed that whenever the slenderness increases, the resulting acceleration increases also. Figure 6 compares the building top displacement response of a three-story building against adjacent buildings with different heights.…”
Section: Resultssupporting
confidence: 93%
“…Kirkwood and Dashti [6] characterized how the building disengagement and ground motion features influence the reaction of adjacent structures founded on a layered, liquefiable soil profile. The dynamic counter actions of adjacent single-degree-of-freedom models were examined by Barrios et al [7] using a laminar box filled with sand. For the dynamic excitation, they executed impulse loads and simulated ground motions.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the entire system behaved elastically, and also footing uplift was not possible. Barrios et al 26 studied the response of two adjacent structures on sand using a small shake table and a flexible soil container. An impulse load and simulated ground motions were considered.…”
Section: Highlightsmentioning
confidence: 99%
“…While the SSI deals with the interaction between individual structures and their underlying soil, the DCI is concerned with the throughthe-soil interaction between adjacent structures within a structure cluster. The SSSI is one of the branches of the SSI, and as a natural protraction, research techniques, including analytical [3][4][5][6][7][8][9][10] , numerical [11][12][13][14][15] and experimental [16][17][18][19][20] methods, that are implemented to investigate the SSSI are similar to those employed in SSI analyses [2] . A real or complete SSI analysis must take into account the possible consideration of interactions with adjacent structures.…”
Section: Introductionmentioning
confidence: 99%
“…Ngo et al [16,58] conducted geotechnical centrifuge tests to investigate the SSSI effects on silica sand, while Hayden et al [59] and Kirkwood et al [18,60] also conducted geotechnical centrifuge tests to investigate the SSSI effects on liquefiable deposits. Barrios et al [17] and Li et al [19] used shaking table tests to examine the SSSI. Gueguen et al [61] applied instrumental records and feild reports to analyze the SSSI after an earthquake.…”
Section: Introductionmentioning
confidence: 99%